An Unusual Case of Acute Appendicitis due to Metastatic Prostatic Adenocarcinoma - Numbereye Numbere; Andrew Dunn; Aaron R. Huber (Case Reports in Pathology)
Acute appendicitis is a common surgical emergency in older adults. In the elderly, like in younger cohorts, acute appendicitis most commonly arises without neoplastic underpinnings. However, the occurrence of acute appendicitis in a patient with a concurrent abdominopelvic malignancy should trigger suspicion for the possibility of a metastatic appendiceal neoplasm. We present the case of a 66-year-old man with a background of a biochemically recurrent prostatic adenocarcinoma who presented to the emergency department with acute appendicitis. Histopathologic examination of the resected appendix revealed an unexpected metastatic spread from his prostatic adenocarcinoma.